What's trending in cloud computing from the internet cybersphere. Issue 10 (7th December 2015) - Oyelude, Adetoun A
Abstract : Purpose: – The purpose of this paper is to examine the following question: What is cloud computing? Design/methodology/approach: – This paper surveys the current literature. Findings: – Cloud computing is described in many ways. Originality/value: – This paper is one of the first pieces to examine the nature of cloud computing.